Experimental and numerical modal analysis of a reduced scale Kaplan turbine model. Issue 1 (1st June 2022) - Roig, R; De La Torre, O; Jou, E; Mulu, B; Escaler, X
Abstract: This paper presents an experimental modal test of a Kaplan turbine model and provides the corresponding analysis of the results. The modal test of the rotor including the runner, the shaft and the generator was performed using, as exciters, an impact hammer and a shaker and, as sensors, several accelerometers. Additionally, numerical models of the rotor with the runner surrounded by air (dry condition) or submerged in water (wet condition) were also built. By comparing the numerical and experimental results, the main modes of vibration of a runner blade in dry conditions and of the rotor shaft both in dry and wet conditions have been identified and discussed. The most significant deviations between experimental and numerical natural frequencies were found around 10% for the rotor shaft and around 6% for the runner blade. Moreover, it was observed that the fourth mode of vibration presents the highest added mass effect with a Frequency Reduction Ratio of about 6.7% and the second mode of vibration shows the lowest damping ratios in both dry and wet conditions with values of about 1.5 and 2.1%, respectively.